HLA class I and II antigens are partially co-clustered in the plasma membrane of human lymphoblastoid cells - Jenei, Attila (The National Academy of Sciences of the USA, 1997)
Major histocompatibility complex (MHC) class II molecules displayed clustered patterns at the surfaces of T (HUT-102B2) and B (JY) lymphoma cells characterized by interreceptor distances in the micrometer range as detected by scanning force microscopy of immunogold-labeled antigens. Electron microscopy revealed that a fraction of the MHC class II molecules was also heteroclustered with MHC class I antigens at the same hierarchical level as described by the scanning force microscopy data, after specifically and sequentially labeling the antigens with 30- and 15-nm immunogold beads. On JY cells the estimated fraction of co-clustered HLA II was 0.61, whereas that of the HLA I was 0.24. Clusterization of the antigens was detected by the deviation of their spatial distribution from the Poissonian distribution representing the random case. Fluorescence resonance energy transfer measurements also confirmed partial co-clustering of the HLA class I and II molecules at another hierarchical level characterized by the 2- to 10-nm Förster distance range and providing fine details of the molecular organization of receptors. The larger-scale topological organization of the MHC class I and II antigens may reflect underlying membrane lipid domains and may fulfill significant functions in cell-to-cell contacts and signal transduction.